Budaya, Ekonomi, Dan Agama Etnis Tionghoa Di Semarang Tahun 1959 - 2000 - Hakim, Muhammad Irfan (Journal of Indonesian History, 2020)
Ethnic Chinese in Indonesia experience many different treatments from native Indonesians. This treatment has emerged since the time when the VOC controlled Indonesia. This treatment resurfaced at the end of the Old Order and during the New Order era until it finally disappeared. When Suharto fell from the presidency, then the Reformation period emerged. In this research, the writer discusses the development of Chinese culture, economy and religion in Semarang. This study uses four stages of historical research methods, namely heuristics, source criticism, interpretation and historiography by analyzing the sources obtained in the field. The result of this research is that Chinese ethbists in Semarang have experienced different treatment in the three periods of government. During the Old Order era they were still free to carry out religious and cultural activities, as well as economically. During the New Order era, cultural and religious activities were prohibited and only economic activities were allowed. During the Reformation era, Chinese ethnic groups were allowed to practice their beliefs and culture and were not limited to the economy..